Women and Anfal (Anfal III for example) is a comparative study in the field of population geography - Talib, Prof.Dr.Jaza Tawfiq; Sadraddin, Asst.L.Kazim Ahmed (Sulaimani Journal for Humanities, 2026)
Women in Garmian were directly and indirectly victims of the Anfal III process. Some of them were killed. In the third Anfal campaign, each of the areas (Duzkhurmatu, Qara Hassan, Qadir Karam, Jabari, Kafri, Kalar, Pebaz, Tilako, Darbandikhan, Sangao, Chamchamal, Takya Kakamand) between (7/4 to 20/4/1988) were heavily affected It is estimated that 43,841 people were killed in Anfal, of which 14,687 were female, accounting for 33.5% of the total number of Anfal victims in Garmian. The aim of the study is to show the demographics of the women who were victims of Anfal III. It also compares the demographics of women before, during and after Anfal and the impact of demographic aspects of Anfal on women in Garmian. To achieve the objectives, the research is divided into three parts. In addition to introducing the research area and determining the geography of Anfal III, referring to Anfal and the geography of Anfal stages and emphasizing women in Anfal Anfal. In order to clarify the issue of women and Anfal, methods (regional, descriptive, comparative) have been used. The study presented several results, such as the demographics of Anfal victims in Garmian and their impact according to labor and economic aspects for age groups: the proportion of females aged 0-14 years is 49.6%, 15-65 years old is 47.1% (3.3%). The fertility rate for women of Anfal victims in Garmian region in pregnancy age between 15-49 years old is 479.8 per thousand. The study makes several recommendations to the government, stakeholders, organizations and scientific centers.
Keywords: Garmian Region; Anfal III; Women and Anfal